PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN PEMBELAJARAN AKTIF KELAS V UPTD SDN 01 KOTO TANGAH SIMALANGGANG - Masyitah Shellyni; Zulfani Sesmiarni; Rodi Rodi; Irmawanti (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) by implementing active learning methods. In this study, an analysis was conducted on the differences in student learning outcomes before and after the implementation of active learning. The method used was an experiment involving two groups: one group that implemented active learning and one control group that used traditional methods. The results of the analysis showed a significant increase in students' academic scores in the group that implemented active learning. In addition, active learning also had a positive impact on student engagement and motivation. These findings indicate that active learning can be an effective strategy in improving PAI learning outcomes. Recommendations are given for further implementation in the education curriculum.